(untitled) (ENTHYMEMA, 2017)
Following Wolfgang Iser’s studies, literary criticism could no longer avoid a confrontation with the phenomenology of the act of reading. This has led the analysis of a literary text towards new researches regarding the reader’s response theory. In particular, it is impossible to define the field of literary investigation, its coordinates and characteristics, without considering the anthropological dimention which defines the epistemological nature of literature itself. We propose in this study a new approach that we call “neurohermeneutic approach”. Unlike an analytical or descriptive approach, the neurohermeneutic approach investigates broth the relations that the reader’s mind establishes with the text figurations and how these figurations stimulates the reader’s mind in that inexhaustible, always new and surprising act of the reading. A partire dagli studi di Wolfgang Iser, la riflessione critica non ha più potuto evitare il confronto con la fenomenologia dell’atto della lettura, e questo ha condotto l’analisi del testo fino alle recenti ricerche in merito alla reader’s response theory. Soprattutto risulta ormai impossibile definire il campo di indagine letterario, le sue caratteristiche e coordinate, a prescindere da un affondo nella dimensione antropologica che definisce la natura epistemologica della letteratura stessa. Proponiamo in questo studio un nuovo approccio che definiamo “neuroermeneutico” e che, a differenza di un approccio analitico o descrittivo, indaga sia le relazioni che la mente del lettore instaura con le figurazioni del testo, sia come queste figurazioni sollecitino la mente del lettore in quell’atto inesauribile, sempre nuovo e sorprendente, della lettura.